Analysis of Reproductive Health Needs Through Focus Group Discussions (FGDs): A Collaborative Outcome of the Early Exposure Program of the President University Faculty of Medicine with Sukamahi Health Center, Mekarmukti Health Center, Lemahabang Health Center, and Cipayung Health Center - Ivan Adrian Montolalu; Emy Tri Dianasari; Zidan Rizqi Adi Nugraha (Jurnal Ragam Pengabdian, 2026)
This study analyzes reproductive health needs in four semi-rural Community Health Centers—Sukamahi, Mekarmukti, Lemahabang, and Cipayung—through a qualitative Focus Group Discussion (FGD) conducted as part of the Early Exposure program of the President University Faculty of Medicine. Twelve participants, consisting of Community Health Center leaders, program managers, health promotion officers, and cadre coordinators, engaged in a structured FGD to explore challenges, gaps, and priorities in reproductive health services. Thematic analysis identified three major themes: (1) fundamental reproductive health needs among adolescents and women, particularly related to puberty, menstrual hygiene, and the lack of adolescent-friendly counseling; (2) gaps in cadre competence, including insufficient training, limited technical skills, and inadequate educational resources; and (3) primary healthcare system constraints, such as limited human resources, weak program coordination, and inadequate service infrastructure. These findings align with reproductive health needs theory, capacity-building frameworks, and primary care determinants. Collectively, the results underscore the need for a targeted intervention focusing on strengthening cadre skills and knowledge in reproductive health. This direction was chosen as the most feasible and high-impact strategy among several alternatives discussed. The study highlights important implications for Community Health Center policy, community health education, and medical student training, while acknowledging limitations regarding sample size and generalizability.